Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan pada PT Bank Mandiri (Persero) Tbk. - Luthfiy Fithriyyah; Vina Anggilia Puspita (Jurnal Simki Economic, 2024)
The aim of this research is to evaluate the financial performance of PT. Bank Mandiri (Persero) Tbk. during the 2020-2022 time period using financial ratios such as liquidity, profitability and solvency ratios. The research method used is quantitative descriptive analysis. The data source used comes from financial reports that are publicly available on the official website of the Indonesia Stock Exchange. The research results show that the impact of the Covid-19 pandemic has greatly influenced the performance of PT. Bank Mandiri (Persero) Tbk. especially visible from the fluctuations that occur in all financial ratios, such as liquidity, profitability and solvency ratios. Despite experiencing these fluctuations, PT. Bank Mandiri (Persero) Tbk. successfully overcome complex economic challenges and wisely manage financial risks.